Need for Knowledge—What, Where and How? How Social Workers Handle Service and Support for Individuals with Disability. (11th February 2022) - Nordgren, Camilla; Anderson, Lotta; Lingärde, Svante; Runesson, Ingrid; Staaf, Annika
Abstract: This article investigates the need and sources of knowledge among LSS administrators in Sweden (i.e. social workers handling service and support for individuals with disability according to the Swedish Disability Act [LSS]). Changing and challenging working conditions and issues concerning professional status warrant the aim. A questionnaire distributed via gatekeepers in a number of municipalities demonstrated that knowledge about 'disability', 'law', 'ethics' and 'augmentative and alternative communication' was rated highly. This result is particularly interesting given that many social work education programmes do not have compulsory courses in disability. Colleagues appear to be relied upon as essential sources of support and knowledge, but the knowledge sharing seems unorganised. Findings are discussed in relation to communities of practice (CoP) and shows that, due to the lack of essential knowledge from formal education and the strong dependence on colleagues, a locally developed praxis might be established. Inadequate theoretical and research-based knowledge, together with this local praxis knowledge, may result in the LSS administrators' work becoming inadequate. A specialist education in disability studies is proposed as a prerequisite for being employed as an LSS administrator, and the inclusion of a theoretical and scientific framework in the regular CoP interaction is also recommended. Abstract : This study analyses the need and sources of knowledge among LSS administrators in Sweden and explores the exercise of public authority aiming at service and support for persons with disability. Knowledge about 'disability', 'law', 'ethics' and 'augmentative and alternative communication' is highly rated. Time is lacking for both competence development and the implementation of new knowledge. Colleagues appear to be essential as sources of knowledge, as the manager seemingly plays a minor role in both the planning and the execution of the skills supply. Knowledge appears to be shared in unorganised ways, depending on individual initiatives and the goodwill of colleagues. Findings are discussed in relation to communities of practice (CoP) and show that, due to the lack of essential knowledge from formal education and the strong dependence on colleagues, a locally developed praxis might be established. Inadequate theoretical and research-based knowledge, together with this local praxis knowledge, may result in the LSS administrators' work becoming inadequate. A specialist education in disability studies is proposed as a prerequisite for being employed as an LSS administrator, and the inclusion of a theoretical and scientific framework in the regular CoP interaction is also recommended.